Exploring the co-occurrence between coastal squeeze and coastal tourism in a changing climate and its consequences. (October 2019) - Lithgow, Debora; Martínez, M. Luisa; Gallego-Fernández, Juan B.; Silva, Rodolfo; Ramírez-Vargas, Debora L.
Abstract: "Coastal squeeze" occurs when there is a chronic loss of coastal habitats landward associated with long-term processes such as sea level rise, land subsidence, sediment deficit and the occupation of space by infrastructure. This phenomenon may also affect socioeconomic activities such as tourism. The goal of this study was to explore the co-occurrence of tourism with coastal squeeze and flooding along the coasts of the Mexican Gulf of Mexico and Mexican Caribbean. Our results reveal that thirty percent of the tourist destinations are exposed to flooding; 62% of the total study area had a moderate to severe degree of coastal squeeze and 66% of the hotels are in squeezed beaches. Finally, we found that most tourist destinations undergoing coastal squeeze are in flood-prone sites, placing communities in high-risk conditions. Different alternatives (such as ecosystem-based protection) to overcome this problem are discussed. Highlights: Coastal squeeze occurs with sea-level rise, increased storminess and a rigid coast. Coastal squeeze may affect tourism because it induces flooding and erosion. Coastal tourism is a growing industry, worldwide, and Mexico is a major player. Tourist sites in the Gulf of Mexico and Caribbean are undergoing coastal squeeze. To overcome this problem ecosystem-based protection could be an alternative.